Analysis of accident-induced congestion in Singapore - Setiawan, Giorgio Alexander (Nanyang Technological University, 2022)
Traffic congestion in urban areas has become one of the most severe problems in practically all modern metropolitan cities. Traffic congestion can be divided into two types based on their causes, which are recurring and non-recurring congestion. Recurring congestion follow a pattern and occur generally at the same time on the same day. Non-recurring congestion happen because of one-time events such as accidents, and they account for more than 50% of total congestion. There has not been sufficient research that provide understanding in accident-induced congestion and hence, that is the aim of this paper.